Késői szüretelésre alkalmas szőlőfajták cukortartalmának és összetételének alakulása az érés során - Sümegi, József; Sümegi , Zsombor; Kispál, Gergő; Láda, Gergő; Véha, Antal; Gyimes, Ernő (Jelenkori Társadalmi és Gazdasági Folyamatok, 2013)
In the last few years more and more people can discover the taste of dessert wine which need special so called "late harvested" grape. This paper present the changes of sugár content (SC) as well the glucose (G) and fructose (F) ratio during ripening. Common case the G and F ratio is 1:1, in the over matured grape the fructose content is higher.